Cannabis use consequences: a multi-ethnic site investigation of risk and protective factors - Gutierrez, Crystal, author; Borrayo, Evelinn, advisor; Prince, Mark, committee member; Davalos, Deana, committee member; Schillington, Audrey, committee member (Colorado State University. Libraries, 2020)
Cannabis is the most popular regulated drug in the world and use rates continue to increase as legalization becomes more prevalent. Heavy cannabis use has been associated with a variety of mental health concerns and psychological distress has been observed to be a risk factor for the development of Cannabis Use Disorder. The current study examines how psychological distress relates to cannabis use consequences across sites in the United States, the Netherlands, Uruguay, Spain, and Argentina. Additionally, this study also explores protective coping strategies that users employ that may reduce the incidence of negative cannabis use consequences. Participants were recruited from university research pools and given surveys that assessed the individual's cannabis use behavior, possible risk and protective strategies, and problematic use outcomes. Results from this study may inform clinical interventions for the treatment and prevention of cannabis use disorder and make suggestions about ways to alter these interventions based on the location of services provided.